(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: A compound is defined as the substance that arises from the mixing of two different substances, and the new materials produced have new properties that differ from the properties of the primary materials. The material produced has a cohesive structure. A compound consists of two basic components, the base material called the "matrix" and the additive called the "filler". The matrix is a polymer, and the filler is different from the type of polymer; it is an inorganic substance like minerals. The filler within the crystalline medium (matrix) is randomly distributed; this occurs because the particle size of the two materials (polymer and filler) are nearly equal and separate when the size of the filler particles is small relative to the size of the polymeric particle. Materials and Methods: The mechanical (hardness and compressive strength) and ultrastructural properties were measured by atomic force microscopy (AFM) for different concentrations of the added nanomaterials are (0, 2.5, 5 and 7.5) wt%. With the casting method, to be used to prepare samples of structural properties, special molds have been used to examine the mechanical properties (hardness and compressive strength), through which the surface can be viewed with high precision very small (100 µm to less than 1 µm) . Compressive strength test is important. It is very important for dental materials as these materials must have mechanical properties similar to the teeth in order to resist chewing forces and it is compressive in a force range of (450-500) newtons. The compressive strength test is very important for dental materials as these materials must have mechanical properties, for the purpose of measuring the compressive strength, cylindrical samples with a diameter of (3 mm) and a thickness of (6 mm). Results: The (AFM) images showed the surface shape of the nanopolymer (PMMA) before and after the addition of nanomaterials, where we notice in a clear picture the increase in the roughness, the mean root value (RMS) and the average particle size. After adding the oxides, and increasing the added proportions, since the roughness when adding nano-oxides is useful for tooth adhesion, and despite the difference in (roughness) values, the values are still less than (200 nm), which was reported as an initial point for the accumulation of bacterial plaques and the risk of incidence of caries and periodontitis, and it can be assumed that the surfaces evaluated in this study have a smooth surface. Which does not represent any risk of scale build-up. We also notice when studying and examining the mechanical properties of hardness, as hardness is the surface resistance to cutting and scratching, as we notice an increase in hardness with increasing concentrations of nanomaterials. The compressive strength test of the nanofilling was also carried out before and after the addition of nanomaterials, as we notice an increase in the amount of compression with the increase in the percentage of addition of nanomaterials as well. These oxides are very safe and harmless to the human body. Conclusion: Samples of novel nanocomposites (PMMA-ZnO-MgO) for dental filling applications have been synthesized. The addition of nanomaterials to the pure polymer leads to an increase in the surface roughness, as well as the roughness rate, the average root value (RMS), and the average grain size with an increase in the proportions of impurities, which leads to an increase in the cohesion and hardness of the filling, as the increase in agglomerations leads to an increase in the cohesion of the filling with the teeth and its durability. While the higher the added percentage, the roughness increased, as we found the highest roughness at (7.5)%, which reached (34.72 nm). Therefore, the filler achieved clear structural properties and a radical change in the structure of the polymer used as a result of the addition of nanomaterials, in addition to durability, quality, safety, and suitability for human tissues. The study showed the mechanical properties and proved that the material (MgO) containing the nano-filling has resistance to the compressive strength test, as it reached the highest resistance to the compressive strength of the addition ratio (7.5)%, which amounted to (150 MPa), while the hardness reached (90.7 MPa) at (7.5%), where The physical properties increase with the increase in the percentage of added nanomaterials.